2015
DOI: 10.1071/an13119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing dietary corn with beet pulp on energy partitioning, substrate oxidation and methane production in lactating dairy goats

Abstract: The objective of this experiment was to study the effect of substitution of corn by beet pulp on energy partitioning, substrate oxidation, nitrogen and carbon balance and milk performance in dairy goats during late lactation. Twelve multiparous lactating Murciano-Granadina goats were fed two diets. Six goats were fed a mixed ration with 310 g/kg DM of ground corn (diet CORN) and in the other diet the corn was substituted with 302 g/kg DM of beet pulp (diet BP) in a cross-over design. No significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is well known that increasing the ratio of concentrate to forage in the diet can reduce the amount of energy loss as enteric CH 4 and this is mainly due to change of fermented substrate from fibre to starch [48]. In an experiment conducted on Murciano-Granadina goats in late lactation, Ibáñez et al [50] observed a lower CH 4 production in goats fed with concentrate (ground corn) diet than beet pulp fed goats. However, concentrate feeding beyond a certain limit is not appreciable as it can cause severe damage to the animal itself and to its production performance.…”
Section: Impact Of Heat Stress On Rumen Functionmentioning
confidence: 99%
“…It is well known that increasing the ratio of concentrate to forage in the diet can reduce the amount of energy loss as enteric CH 4 and this is mainly due to change of fermented substrate from fibre to starch [48]. In an experiment conducted on Murciano-Granadina goats in late lactation, Ibáñez et al [50] observed a lower CH 4 production in goats fed with concentrate (ground corn) diet than beet pulp fed goats. However, concentrate feeding beyond a certain limit is not appreciable as it can cause severe damage to the animal itself and to its production performance.…”
Section: Impact Of Heat Stress On Rumen Functionmentioning
confidence: 99%
“…Then the mixed solution was distilled by steam and 150-200mL of distillate was collected in an Erlenmeyer flask. The distillate was then titrated with 0.1mol L -1 sodium hydroxide solution to measure the concentration of total VFA (Kromann et al 1967, Ibáñez et al 2014.…”
Section: Rumen Fluid Samplesmentioning
confidence: 99%